Horizontal transfer of blaTEM, blaCTX-M and class 1 integron genes from uropathogenic Escherichia coli to E. coli DH5α - Javed, Saima (International Journal of Pathology, 2020)
Background: Emerging antibiotic resistance in uropathogenic E. coli (UPEC) is a global problem that results in treatment failure. Mobile genetic elements are key players in dissemination of antibiotic resistance genes via horizontal gene transfer (HGT).Objective: This prospective study was designed to investigate the possible role of HGT (via conjugation process) in spread of antibiotic resistance genes from MDR-UPEC strains to sensitive strain of E. coli DH5α.Materials and Methods: This study was performed at the Department of Microbiology, University of Karachi from February to July 2019. Four UPEC strains belonging to different phylogenetic groups A, B1, B2 and D were selected for conjugation assay. Sodium azide resistance was induced in E. coli DH5α for the study. Transconjugants were confirmed phenotypically by disc diffusion method and genotypic confirmation was done by PCR method.Results: E. coli DH5α was successfully induced for sodium azide resistance. Conjugation experiment proved that blaCTX-M, blaTEM and class 1 integron genes were transferred from MDR-UPEC isolates to E. coli DH5α. Conclusion: The current study concludes that drug resistant genes blaTEM, blaCTX-M and class 1 integron genes may be transmitted from donor MDR UPEC to recipient strain of E. coli DH5α via HGT.